A Feasibility study on eyeReader an eye-gaze tracking device and service - Callanta, Robert John; Celiz, Mary Angelique; Gutierrez, Ria Mae; Ramos, April Rose (College of Engineering, 2013)
This feasibility study was conducted to examine the potential of the eyeReader Device and Service, if it is capable to be mass produced and released in the market that will ensure revenue, provided proper funding by the right investors. The eyeReader is a device that screens the eye movement. It uses an Eye-Gaze Tracking Technology that can be of use to applications where in eye gaze and fixations are needed. The mission of the company is to aid and assist children concerning their special needs which can be tracked with eye-gaze technology, to offer evaluation procedures to advertising agencies that would help them in improving their business, and to provide support for psychologists and psychiatrists in assessing mentally and psychologically handicapped patients. The company envisions being the premier supplier of eye tracking technology in the Philippines within the next 5 years. The market analysis showed a gap in the demand for the technology. This being only available abroad, the need for production in the Philippines is adamant because of the growing number of special children who can avail of the service. The costs of production are relatively much lower than the perceived price if bought abroad. The primary market is the learning and psychology sector, which includes the speech pathologists, psychologists, and those in the special education industry. The secondary market on the other hand includes the market research industry and the advertising industry, which will only be focused on starting from the second year of business which would be on year 2015. The results show the key points of the eyeReader as a product and service and how it can serve potential consumers. The marketing strategies were then developed to make sure the product reaches full potential. Lastly, the sales and marketing costs were determined to account for the superior technology. It was concluded that the product is market feasible. The technical study included the product information, and on how it is offered as a product and service. From the 3 supplier alternatives, it was decided that procurement of materials should come from Alexan. All equipment and tooling were also laid out for use in the production. Capacity planning showed that all of the process was to be made by the company, except for the packaging, which would be outsourced. After-sales support procedures and warranty were then determined. The facility is located in Cubao with an area of 200 square meters. The cost analysis showed that adding together the operating expenses, capital expenditures, pre-production expenses, and marketing cost would amount to 3.5M php for the first year. It is concluded that the product is technically feasible. In the organization management study, it been deduced that the company is ought to be a corporation. Thus, investors are needed to sustain the business. Even with the small market, a high projected income is expected. Job descriptions of each of the workers were identified, as well as their compensations and benefits. The financial study enabled the company to see all financing requirements. It was shown that capital could be raised through borrowing the 70% from financial institutions (loans, etc.) and 30% would come from equity. The loan will be borrowed from a financing institution offering a loan of payment terms with annual 15% interest rate within 5 years. With cash flows already in effect by the end of the first year, the loan could easily be paid. Tax was considered in the final computation of revenue. Financial projections were laid out by the use of pro-forma income statement, cash flow projections, and balance sheet. Financial ratios were also computed to show profitability and operating efficiency in the future, in the sensitivity analysis, the payback period showed that the company can be free of debt by the early months of the second year of business. The computed Net Present Value and IRR were very high for the company, which meant that business is acceptable for the years to come. The breakeven analysis also showed good breakeven points for each year's production. Summarizing the results of these projections confirmed the financial feasibility of the product. The socio-economic profitability of the product gave importance to the generation of jobs, government contribution through tax, and its value to the customers which is signified by the relatively much lower price compared to the ones sold abroad. Overall analysis of the said studies confirm that the production of eyeReader in the Philippines is wholly feasible, in terms of marketability, technicality, and financial.